2007
DOI: 10.1016/j.jcrs.2007.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment changes with age and during accommodation measured with partial coherence interferometry

Abstract: In addition to forward movement of the anterior lens surface with age, the posterior surface moved backward. Alterations in LT and ACD sufficient for a unit of refractive power change during accommodation might be smaller than previously thought. Anterior shifting of the lens may also participate in the accommodative response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
7
42
1
Order By: Relevance
“…A number of studies (Table 1) have assessed the changes in central ACD during accommodation. Our results are in agreement with those found previously in emmetropic volunteers (4,15,17,18,22,23,25,26) . Bolz et al (4) , who used partial coherence interferometry, found a relative ACD decrease of 4.92% after -4.00 D of vergence.…”
Section: Anterior Chamber Depthsupporting
confidence: 93%
See 1 more Smart Citation
“…A number of studies (Table 1) have assessed the changes in central ACD during accommodation. Our results are in agreement with those found previously in emmetropic volunteers (4,15,17,18,22,23,25,26) . Bolz et al (4) , who used partial coherence interferometry, found a relative ACD decrease of 4.92% after -4.00 D of vergence.…”
Section: Anterior Chamber Depthsupporting
confidence: 93%
“…The ACD obtained after -6 D accommodation was 5% shallower than that measured for far vision. Malyugin et al (17) , Read et al (23) , and Tsorbatzoglou et al (25) studied changes in ACD after -3.00 D of accommodation and found that the relative changes were 3.80%, 3.20% and 2.23%, respectively. Finally, Ni et al (18) and Read et al (22) also studied the changes in ACD with accommodation in young eyes with the help of Pentacam HR.…”
Section: Anterior Chamber Depthmentioning
confidence: 99%
“…We demonstrated that beside the age-related material and geometric properties, the effect of the refractive index of the lens is also important (Figure 15). If we compare our numerical results with values measured by Tsorbatzoglou et al (2007) [21] based on defocusing technique, we obtain the following diagram (see also Figure 15). Subjects were divided into 3 age groups: younger than 30 years (Group 1), between 31 years and 44 years (Group 2), and older than 45 years (Group 3).…”
Section: Discussionmentioning
confidence: 85%
“…These applied data are mostly based on literature values. Finally, the calculated values will be compared to measurement results of Tsorbatzoglou et al (2007). [21] 2 Materials and methods Numerical simulations are carried out with the ANSYS Mechanical APDL code.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation